Effectiveness of Serum and Whole blood for Rapid HIV Testing in Pregnant Women at Batang Beruh Community Health Center - Nur Afni Heryanti Octavia; Rima Dhani Puspita (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
Human Immunodeficiency Virus (HIV) remains a global health problem, particularly among pregnant women due to the risk of mother-to-child transmission. Rapid HIV testing is widely used for early detection in primary healthcare settings. Different blood specimens such as serum and whole blood can be utilized; however, their effectiveness requires evaluation. Objective to determine the effectiveness of serum and whole blood specimens in rapid HIV testing among pregnant women at Batang Beruh Health Center. Methods: This study employed a cross-sectional analytical design involving 20 pregnant women undergoing rapid HIV testing. Examination was performed using serum and whole blood specimens. Data were analyzed using Chi-square test with a significance level of 0.05. Results: Sixteen respondents (80%) showed good examination results consisting of 8 non-reactive serum results and 8 non-reactive whole blood results. Four respondents (20%) were categorized as poor results with reactive findings in both specimen types. Chi-square analysis showed p=0.02 (<0.05), indicating significant effectiveness of serum and whole blood usage. Serum and whole blood specimens are effective for rapid HIV testing among pregnant women.